IMPLEMENTASI MANAJEMEN KONFLIK DALAM PENYELESAIAN MASALAH WALI MURID DAN TENAGA PENDIDIK DI SMPT FAJRUL ISLAM - Sidik Amin; Ade Ikbal Pauji; Amarullah Malik (Manajerial | Journal Manajemen pendidikan islam, 2024)
Educational institutions may face various problems and conflicts involving several parties, such as students, teachers, and parents of students. Conflicts usually arise because of differences of opinion, values, knowledge, or perhaps because of different interests between individuals or groups involved. A conflict that is not handled properly will have a negative impact on the learning process and daily activities at school. Conflict in an educational institution will definitely occur, but how is the method or attitude of the institution in resolving the conflict that occurs. This study was conducted to examine the Implementation of Conflict Middle School with a research focus on several points. First, What triggers conflict in schools can occur. Second, How is the Implementation of Conflict Management carried out in solving problems. Third, What are the supporting and inhibiting factors in solving problems or conflicts. In this study, the approach used by the researcher is a qualitative approach with a descriptive field research type. Data sources obtained through interviews, observations, and documentation. Meanwhile, the informants in this study were the principal, vice principal for student affairs, guidance and counseling teachers, guardians and students. The results of the study showed that: first, the trigger for the conflict between guardians and educators was student delinquency which was caused by misunderstandings that occurred due to incomplete information. Second, the implementation of conflict management carried out by the school through mediation and deliberation between the two parties to find a solution that did not harm anyone. Third, the supporting factors in resolving the conflict that occurred were the openness of information from both parties, while the inhibiting factors were the involvement of third parties and the busyness of parents or guardians of students in carrying out their activities.